THE IMPACT OF CULTURAL BACKGROUND ON IDIOM COMPREHENSION IN EFL LEARNERS - Norpoʻlatova Nozima Yusufxon qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Annotation: This article explores the impact of cultural background on idiom comprehension among English as a Foreign Language (EFL) learners, with a special focus on the challenges faced by learners from culturally diverse contexts. Idioms, as culturally bound expressions, present considerable difficulties for language learners due to their figurative meanings, cultural references, and context-dependent usage. The research highlights how cultural knowledge, exposure to authentic language input, and learners’ L1 conceptual systems influence their ability to interpret and correctly use English idioms. A case study involving Uzbek EFL learners is presented to illustrate the relationship between cultural familiarity and idiomatic competence. Findings reveal that limited cultural schema, literal translation strategies, and insufficient exposure to English-speaking culture negatively affect idiom comprehension. The article concludes with pedagogical recommendations for integrating cultural awareness and idiom instruction into EFL curricula to enhance learners’ communicative competence.